2013
DOI: 10.1166/jbn.2013.1493
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Functional Magnetic Nanoparticles Mediated with PEG-4000 and Application in <I>Pseudomonas Aeruginosa</I> Rapid Detection

Abstract: A rapid detection method of Pseudomonas aeruginosa based on magnetic separation and chemiluminescence was developed in this paper. Magnetic nanoparticles (MNPs) were prepared by solvothermal method with PEG-4000 as a surfactant, and then were modified. The prepared MNPs present a uniform morphology and good dispersion. The sizes of MNPs can be controlled by adjusting the dosage of FeCl3 x 6H2O. The obtained particles were characterized with Scanning electron microscope (SEM), Transmission electronic microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…A tube containing the reaction mixture and sterile water was included in all reactions as a negative control. The PCR products were analysed by electrophoresis (1.5 % agarose gel) 22-24.…”
Section: Methodsmentioning
confidence: 99%
“…A tube containing the reaction mixture and sterile water was included in all reactions as a negative control. The PCR products were analysed by electrophoresis (1.5 % agarose gel) 22-24.…”
Section: Methodsmentioning
confidence: 99%
“…Functionalization of the CNTs with magnetic Fe 3 O 4 nanoparticles (NPs) has been suggested to be very important in developing the targeting ability of the oxidized-CNTs. The multifunctional properties of the Fe 3 O 4 NPs, such as small size, high magnetic responsivity and low toxicity, [34][35][36][37][38][39][40][41][42][43] can be used to increase the accumulation of drugs in pathological sites, thereby reducing the non-specific toxicity and some other adverse side-effects. We therefore decorated the MWNTs with Fe 3 O 4 NPs to ensure a strong magnetic responsiveness and provide the targeted property for various applications.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10] Besides these, multiple reports have found that vd-siRNAs could also target host mRNA in a sequence-specific manner, resulting Copyright: American Scientific Publishers in silencing of the homologous host genes and subsequent viral symptom development. [11][12][13][14][15][16][17][18] For example, vdsiRNAs derived from the Cauliflower mosaic virus 35S leader sequence could specifically down-regulate the Arabidopsis At1g76950 transcript. 19 VsiRNAs from Tobacco mosaic virus Cg could specifically cleave At1g30460 and At2g16595 transcripts; 20 Vd-siRNAs from the Y-satellite of Cucumber mosaic virus (CMV) could specifically cleave the Nicotiana benthamiana ChlI mRNA and resulting in bright yellow symptoms.…”
Section: Introductionmentioning
confidence: 99%